A Critical Review of the Book English in Educational Administration - Vida Rahiminezhad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Educational administration is generally meant planning, organizing, guiding, coordinating, supervising, and evaluating the educational process, but specifically it means guidance, assistance, and creating the right environment for the educational activity. In other words, educational administration is the process of harmonizing human talents and taking advantage of environmental conditions for educational purposes. The aim of this article is to criticize the book entitled English in Educational Administration. This book could help students to become familiar with the specialized vocabulary of Educational Administration in order to study research done in this area. It is found out that this book is not only an academic text, but it includes the characteristics of teaching and learning, as well. Findings show that along with several positive points in this book, a few shortcomings also point out, and some suggestions are provided to improve the textbook, such as to use up-to-date materials that contain less complex and long sentences and also to provide a section called “Further Reading” at the end of each lesson or at the end of the book to help students who need more information about the discussed points.